The Three Faces of Labor: Sustainability and the Next Wave of Automation. Issue 2 (3rd April 2019) - Greenwood, Daphne T.
Abstract: This article develops a model of three faces of labor from Figart, Mutari, and Power's three faces of wages. This is integrated with sustainability models to locate the process of human and social capital formation and explore issues arising from technological change. The latest wave of automation, involving robotics and artificial intelligence, is expected to be an even greater challenge for worker well-being than globalization and immigration. The model supports a new narrative around labor that incorporates the caring economy as well as a framework for thinking about labor issues and long-term well-being.